Response of Male Lambs to Concentrate Mixtures given with or without Natural Clay under Egypt Conditions - Marai, Eayez M; Bhgat, L B; Shalaby, T H; Abdel_Hafez, M A (Annals of Arid Zone, 2016)
Lambs given diets containing concentrate mixture without roughages were better in daily weight gain, economical and feed efficiencies, carcass weight, dressing percentage and lying time than those fed on diets containing roughages. However, , contrary trends were found in. case of filled gut, eating time, rumination time, frequencies of drinking water, micturition, defecation, mounting and licking block minerals, rectal temperature and respir3tion rate, with the same treatment. Lambs given diets containing natural clay surpassed those not given natural clay in final weight, daily gain weight, economical efficiency, feed efficiency, water intake, eating time, rumination time, lying time and frequencies of drinking water and mounting. While, contrary trends were shown in defecation frequency, licking block minerals frequency, rectal temperature and respiration rate. The full concentrate mixture diet (without roughages) plus natural clay surpassed the other diets in final weight, daily weight gain, economical and feed efficiencies, dressing percentage and lying time. On the other hand, lower values were recorded in case of empty gut weight, eating time, rumination time, frequencies of drinking water, defecation, mounting and licking block minerals, rectal temperature and respiration rate, with the same treatment. T3 was significantly lower in lambs fed concentrate mixture alone than in the other diets. At the same time, T4 was significantly higher in lambs fed the diets containing concentrate + roughages than in those fed the other. diets.